2022
DOI: 10.2147/idr.s378524
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Derived Smart Watches and Mobile Phones are Contaminated Niches to Multidrug Resistant and Highly Virulent Microbes

Abstract: Background As high touch wearable devices, the potential for microbial contamination of smart watches is high. In this study, microbial contamination of smart watches of healthcare workers (HCWs) was assessed and compared to the individual’s mobile phone and hands. Methods This study was part of a larger point prevalence survey of microbial contamination of mobile phones of HCWs at the emergency unit of a tertiary care facility. Swabs from smart watches, mobile phones a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Subsequent work reported that SARS-CoV-2 was found to be viable on mobile phones for up to 28 days [3]. Furthermore, viability cultures and metagenomic analysis of mobile phone derived swab samples from healthcare providers has demonstrated that these devices are an important fomite [2,[4][5][6][7]. In addition to the extensive microbial community detected, metagenomic-based studies have also uncovered a large resistome and virulome, comprising genes for antibiotic resistance and virulence factors, respectively [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent work reported that SARS-CoV-2 was found to be viable on mobile phones for up to 28 days [3]. Furthermore, viability cultures and metagenomic analysis of mobile phone derived swab samples from healthcare providers has demonstrated that these devices are an important fomite [2,[4][5][6][7]. In addition to the extensive microbial community detected, metagenomic-based studies have also uncovered a large resistome and virulome, comprising genes for antibiotic resistance and virulence factors, respectively [5].…”
Section: Introductionmentioning
confidence: 99%
“…Mobile phones may be vectors for microbial dissemination and as such pose a signi cant threat for the spread of antibiotic resistant and highly virulent organisms globally, impacting biosecurity and national public health [4]. In 2017, the World Health Organisation published a catalogue of 12 families of bacteria that pose the greatest threat to human health to foster research and development of novel antibiotics [8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, our findings are consistent with another study, which detected similar microbial species on health care-derived smart watches and also confirmed the presence of antibiotic-resistant strains among these species. 5 One potential limitation is that participants' awareness of being monitored during Phase 2 could have influenced their behavior, resulting in increased caution toward preventing the transfer of microbes. Still, 4 of 7 participants were observed to have transferred microbes, suggesting that microbial transfer is an even more frequent occurrence than we have presented in this study.…”
mentioning
confidence: 99%